Toxocara: The Enigmatic Parasite 2006
DOI: 10.1079/9781845930264.0211
|View full text |Cite
|
Sign up to set email alerts
|

Exposure and environmental contamination.

Abstract: This chapter focuses on soil contamination of Toxocara eggs with particular reference to their survival on the soil surface. In addition, this chapter discusses type of soil and egg prevalence, Toxocara canis and T. cati egg discrimination, exposure and countermeasures. The conclusions are summarized as follows: (1) soil contamination with the eggs of Toxocara spp. occurs worldwide, irrespective of socioeconomic and developmental status; (2) there is a clear connection between the degree of soil contamination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 0 publications
1
28
0
3
Order By: Relevance
“…Seroprevalence surveys indicate that 3-7% of healthy adults and 15-23% of children typically have detectable antibodies to Toxocara (Won et al 2008;Romano et al 2010;Rubinsky-Elefant et al 2010), but higher values have been recorded from the tropics (Mizgajska 2001;Colli et al 2010). Studies from all over the world demonstrated high rates (10-30%) of soil contamination with Toxocara eggs in backyards, sandpits, parks, playgrounds, lake beaches, and other public places (Mizgajska-Wiktor and Uga 2006). Mizgajska (2001) concluded that the prevalence of human toxocarosis is proportional to soil contamination with infective eggs of Toxocara spp.…”
Section: Introductionmentioning
confidence: 93%
“…Seroprevalence surveys indicate that 3-7% of healthy adults and 15-23% of children typically have detectable antibodies to Toxocara (Won et al 2008;Romano et al 2010;Rubinsky-Elefant et al 2010), but higher values have been recorded from the tropics (Mizgajska 2001;Colli et al 2010). Studies from all over the world demonstrated high rates (10-30%) of soil contamination with Toxocara eggs in backyards, sandpits, parks, playgrounds, lake beaches, and other public places (Mizgajska-Wiktor and Uga 2006). Mizgajska (2001) concluded that the prevalence of human toxocarosis is proportional to soil contamination with infective eggs of Toxocara spp.…”
Section: Introductionmentioning
confidence: 93%
“…With a small garden shovel marked down with color lines to a depth of three cm, sampletakers dug square-shaped holes three cm deep, then collected the soil sample and placed it into plastic bags. 7,8 Where sample-takers noted that the soil was less dense, they dug below 3 cm to get a sample. They used air-tight plastic bags to store the samples.…”
Section: Figure 1 Demonstration Of the Examined Areas Throughout Attmentioning
confidence: 99%
“…Before becoming infective, the ova undergo further development in the soil and can be viable for several years. Children are the most vulnerable ones because of their habit of playing with soil or objects contaminated with eggs [ 2 ]. Toxocara causes visceral larval migrans characterized by migration of larvae to different organs including the eyes and brain.…”
Section: Introductionmentioning
confidence: 99%